Efektivitas Penyidikan dan Pemberantasan Peredaran Narkotika Pada Badan Narkotika Nasional Provinsi Sumatera Selatan - Kurniawan, Ahmad Kurdi; Sulastri, Sri; Mardianto, Mardianto (@-Publik: Jurnal Administrasi Publik, 2021)
The purpose of this study was to determine and analyze the effectiveness of the investigation and eradication of narcotics trafficking at the National Narcotics Agency of South Sumatra Province This study uses a descriptive method with a qualitative approach. Data or information is collected through interviews with informants. The types of data used in this study include qualitative data types obtained from interviews with informants as well as books, regulations, documents, journals and other literature deemed relevant to this research. Data collection techniques used include interviews, observation and documentation. The data analysis technique used includes three components of analysis, namely reduction, data presentation and drawing conclusions. The results showed that the effectiveness of investigating and eradicating narcotics trafficking at the National Narcotics Agency of South Sumatra Province according to the indicators used by researchers was quite good. However, it needs to be improved. So, the BNNP of South Sumatra cannot be said to be effective. it can be concluded that a) Inputs; In achieving this target, his party has done as much as possible but it has not been so effective and not optimal. This is because the modus operandi is getting more sophisticated and the capabilities of the apparatus are limited, including equipment and in particular the limited budget for minimal funds, only for core operational activities, human resources (HR) in quantity are very lacking, the limitations of supporting tools and infrastructure in the investigation process and patrol equipment are becoming a problem. one of the obstacles in eradicating narcotics is considering the geographical conditions of the densely populated province of South Sumatra and the congested road conditions and the methods and strategies used are appropriate but not optimal in their implementation. b) Process; The National Narcotics Agency of South Sumatra Province has complied with procedures and also the BNNP of South Sumatra continues to maximize the mechanism and process of the investigation by collecting existing information and evidence and the Eradication of Narcotics Circulation is carried out in collaboration with the community and local government, socialization has been carried out and at the stage of supervision and enforcement it is sufficient good but not optimal due to the lack of available human resources. and c) Results; Investigations and Eradication of Narcotics Circulation at the National Narcotics Agency of South Sumatra Province have produced results but are not yet very effective. This is evident from the number of disclosures of cases in 2019 and 2020 that are still small, even though there are results of case disclosures